Molecular clonings and sequences of Djungarian (Phodopus sungorus) and Chinese (Cricetulus griseus) hamster interferon-gammas - Ike, K. (Nippon Veterinary and Animal Science Univ., Musashino, Tokyo (Japan)); Uchida, Y; Morita, T; Imai, S (Journal of Veterinary Medical Science, 2003)
Djungarian (Phodopus sungorus) and Chinese (Cricetulus griseus) hamster IFN-v genes were cloned and sequenced. The Djungarian and Chinese hamster genes were both 525bp nucleotides, resulting in 174 amino acids in full length with a predicted molecular weight (MW) of 19,560 dal and 19,775 dal, respectively. The first 23 amino terminal amino acids consisted of a hydrophobic signal sequence when cleavaged, which would result in a mature 151 amino acid polypeptide with a predicted MW of 17,1 15 dal in the Djungarian hamster IFN-v and 17,255 dal in the Chinese hamster one.